Extended SO2 outgassing from the 2014–2015 Holuhraun lava flow field, Iceland - Simmons, Isla; Pfeffer, M. A.; Calder, Eliza; Galle, Bo; Arellano, Santiago; Coppola, D.; Barsotti, S. (Bulletin of Volcanology, 2017)
The 2014–2015 Holuhraun eruption was the largest fissure eruption in Iceland in the last 200 years. This flood basalt eruption produced ~ 1.6 km3 of lava, forming a lava flow field covering an area of ~ 84 km2. Over the 6-month course of the eruption, ~ 11 Mt of SO2 were released from the eruptive vents as well as from the cooling lava flow field. This work examines the post-eruption SO2 flux emitted by the Holuhraun lava flow field, providing the first study of the extent and relative importance of the outgassing of a lava flow field after emplacement. We use data from a scanning differential optical absorption spectroscopy (DOAS) instrument installed at the eruption site to monitor the flux of SO2. In this study, we propose a new method to estimate the SO2 emissions from the lava flow field, based on the characteristic shape of the scanned column density distribution of a homogenous source close to the ground. Post-eruption outgassing of the lava flow field continued for at least 3 months after the end of the eruption, with SO2 flux between < 1 and 9 kg/s. The lava flow field post-eruption emissions were not a significant contributor to the total SO2 released during the eruption; however, the lava flow field was still an important polluter and caused high concentrations of SO2 at ground level after lava effusion ceased.